Benzofuro[3, 2-d]pyrimidines inspired from cercosporamide CaPkc1 inhibitor: Synthesis and evaluation of fluconazole susceptibility restoration. Issue 13 (15th July 2018) - Dao, Viet Hung; Ourliac-Garnier, Isabelle; Bazin, Marc-Antoine; Jacquot, Catherine; Baratte, Blandine; Ruchaud, Sandrine; Bach, Stéphane; Grovel, Olivier; Le Pape, Patrice; Marchand, Pascal
Graphical abstract: Highlights: Heterocyclic compounds inspired from cercosporamide were synthesized. Synergistic effect with fluconazole on inhibition of cell growth of a Candida albicans resistant strain is reported. Kinase inhibitory activity was detected. Abstract: In a context of growing resistance to classical antifungal therapy, the design of new drugs targeting alternative pathways is highly expected. Benzofuro[3, 2- d ]pyrimidine derivatives, derived from (−)-cercosporamide, were synthesized and evaluated as potential Candida albicans PKC inhibitors in the aim of restoring susceptibility to azole treatment. Co-administration assay of benzofuropyrimidinedione 23 and fluconazole highlighted a synergistic effect on inhibition of cell growth of a Candida albicans resistant strain.